Fine Companions: Critical Realism and Framework Analysis - Jayne M; Jackie S; Munford R (SAGE Publications, 2023)
This article discusses the alignment of framework analysis with a critical realist philosophy in qualitative analysis. Whilst both are used in social sciences and prioritise meaning making of complex phenomena, the two approaches have not been combined prior to the study outlined in this article. The article describes critical realist ontology and epistemology, the implications of this philosophy for data analysis and the structured processes of framework analysis. Using an example from a study of youth programmes in Aotearoa/New Zealand, the article demonstrates the value of framework analysis for critical realist studies. Emphasis is placed on the capacity of framework analysis to support varied foci on data, theory, and different modes of inferencing which are used in critical realist studies to provide an explanatory account of data.
Keywords: critical realism; framework analysis; qualitative data analysis; youth programmes; positive youth development; Aotearoa/New Zealand